Prioritizing Minangkabau Cultural Features for Contextual English Materials: An Elementary Teachers’ Needs Analysis - Meisyani Gustri Fadila; Yenni Rozimela; Yetti Zainil (JEE (Journal of English Education), 2026)
The Merdeka Curriculum promotes early English proficiency in elementary school students. However, learning English as a foreign language is still difficult for young learners, especially in terms of acquiring the vocabulary and understanding the basic language abilities. Therefore, English teaching materials should be contextualized with content relevant to students’ social backgrounds. Despite the growing focus to the integration of local culture into English language education, only a few research have indicated which cultural aspects for English material development in elementary schools should be given priority. This study identified and prioritized Minangkabau cultural traits for elementary school teachers’ contextual English material development to meet their needs. An explanatory sequential mixed-methods design was used to collect data from elementary school teachers in Lengayang District, West Sumatra, where Minangkabau culture is strongly rooted in students’ daily lives. Descriptive statistics were used to evaluate quantitative data and theme analysis was used to analyze qualitative data. The results demonstrated that the integration of Minangkabau culture into English learning materials was strongly supported. The most emphasized cultural attributes were traditional games, folktales, traditional clothes, and traditional meals, as they were believed to enable vocabulary learning, boost student engagement, promote cultural awareness, and assist meaningful language use. The study concluded that the emphasis on culturally relevant content can be useful in developing contextual and culturally responsive English materials for students in elementary schools.